Withaferin A attenuates lipopolysaccharide-induced acute lung injury in neonatal rats - Gao, S; Li, H; Zhou, X-Q; You, J-B; Tu, D-N; Xia, G; Jiang, J-X; Xin, C (Cellular and Molecular Biology, 2015)
Withaferin A (WFA) is an active compound from Withania somnifera and has been reported to exhibit a variety of pharmacological activities such as anti”inflammatory, immunomodulatory and anti”tumor properties. In the present study, we investigated the potential protective role of WFA on acute lung injury in neonatal rats induced by lipopolysaccharide (LPS). We found that WFA significantly attenuated the pathological changes of lungs induced by LPS injection. Administration with WFA obviously decreased pulmonary neutrophil infiltration accompanied with decreased MPO concentrations. WFA also reduced the expression of pro”inflammatory cytokines including MIP”2, TNF”Î±, IL”1Î² and IL”6. Meanwhile, the expression levels of anti”inflammatory mediators such as TGF”Î²1 and IL”10 were significantly increased following WFA administration. Moreover, WFA protected LPS”treated rats from oxidative damage via up”regulation of TBARS and H2O2 concentrations and down”regulation of ROS contents. Taken together, the present study demonstrated that WFA administration attenuated LPS”induced lung injury through inhibition of inflammatory responses and oxidative stress.